The Significance of Nanofluids as Working Fluids in Energy Extraction Process on Geothermal Heat Exchanger System Utilizing Abandoned Oil Wells: A Review - Prihtiantoro, Dedhy; Maula, Mohamad Izzur; Imaduddin, Fitrian (Testing Center for Oil and Gas LEMIGAS, 2026)
Geothermal energy offers significant potential as an environmentally friendly renewable resource; however, large-scale deployment remains constrained by high drilling and infrastructure costs. Repurposing abandoned oil and gas wells as geothermal heat exchanger systems has emerged as a promising alternative, yet research on the application of nanofluids in such systems remains limited and fragmented. This review employs a narrative synthesis approach to analyze more than 80 peer-reviewed studies related to wellbore geothermal heat exchangers, working fluids, and nanofluid thermal enhancement mechanisms. The review identifies a clear knowledge gap regarding the integration of nanofluids into geothermal heat extraction processes in deep coaxial and U-tube systems, particularly with respect to long-term stability, pressure drop, and techno-economic feasibility. Findings indicate that nanofluids, especially metal-oxide and hybrid formulations, can substantially enhance thermal conductivity and heat transfer performance, with TiO₂- and CuO-based nanofluids showing the most promising results. However, challenges remain in optimizing concentration, ensuring stability, and mitigating increased pumping power. Overall, this review provides a consolidated understanding of existing research and highlights key directions for future development to improve heat extraction efficiency in geothermal systems utilizing abandoned wells.